Epidemiological investigations of diarrhea in children in Praia city, Cape Verde - Colito, Denise Andrade; Dorta-Guerra, Roberto; Da Costa Lima, Hailton Spencer; Pina, Carine; Gonçalves, Deisy; Valladares, Basilio; Foronda, Pilar (Frontiers in Microbiology, 2022)
Diarrheal disease is a major cause of infant mortality and morbidity in Africa and results primarily from contaminated food and water sources, but its prevalence predictors in Cape Verde are not completely known. For this reason, this study aimed to identify the etiological agents of diarrhea in Cape Verdean children and assess its associated risk factors. A survey questionnaire was used, and a total of 105 stool samples from children with diarrhea aged 0 to 12 years at the Central Hospital of Praia (Santiago, Cape Verde) were analyzed. The analyses were carried out using Biofire FilmArray Gastrointestinal Panels. Possible risk factors for these pathogens were analyzed using logistic regression, chi-square tests, or Fisher's exact test. Among the bacteria, enteroaggregative Escherichia coli (45.71%; 95% CI: 36.71 - 56.70), enteropathogenic E. coli (40%; 95% CI: 30.56 - 50.02), Shigella/enteroinvasive E. coli (29.52%; 95% CI: 21.02 - 39.22), E. coli enterotoxigenic (12.38%; 95% CI: 6.76 - 20.24), Campylobacter sp. (10.48%; 95% CI: 5.35 - 1.97), Vibrio sp. (4.76%; 95% CI: 1.56 - 10.76), Clostridioides difficile (3.81%; 95% CI: 1.05 - 9.47), Vibrio cholerae (2.86%; 0.59 - 8.12), Shiga-like toxin-producing E. coli (2.86%; 0.59 - 8.12) and Salmonella sp. (0.95%; 0.02 - 5.19) were identified; four viruses, Rotavirus A (28.57%; 95% CI: 20.18 - 38.21), Sapovirus I. II. IV and V (11.43%; 95% CI: 6.05 - 19.11), Norovirus GI.GII (6.67%; 95% CI: 2.72 - 13.25) and Adenovirus F 40.41 (6.67%; 95% CI: 2.72 - 13.25) were also observed. All the pathogens detected in this study were found in coinfections. Significant associations with risk factors were found; specifically, having a bathroom at home reduced the risk of Campylobacter sp., having animals at home increased the risk of Shigella/EIEC infection, and drinking bottled water reduced the risk of Sapovirus infection. From the findings of this study, it can be concluded that, in Cape Verde, there is a high prevalence and diversity of pathogens among children. Our results could help to establish an adequate diagnosis and effective treatments for diarrheal disease.